Potential Surviving Effect of Cleome droserifolia Extract against Systemic Staphylococcus aureus Infection: Investigation of the Chemical Content of the Plant - Jawaher Alqahtani; Walaa A. Negm; Engy Elekhnawy; Ismail A. Hussein; Hassan Samy Hassan; Abdullah R. Alanzi; Ehssan Moglad; Rehab Ahmed; Sarah Ibrahim; Suzy A. El-Sherbeni (MDPI AG, 2024)
The increasing rates of morbidity and mortality owing to bacterial infections, particularly Staphylococcus aureus have necessitated finding solutions to face this issue. Thus, we elucidated the phytochemical constituents and antibacterial potential of Cleome droserifolia extract (CDE). Using LC-ESI-MS/MS, the main phytoconstituents of CDE were explored, which were kaempferol-3,7-O-bis-alpha-L-rhamnoside, isorhamnetin, cyanidin-3-glucoside, kaempferide, kaempferol-3-O-alpha-L-rhamnoside, caffeic acid, isoquercitrin, quinic acid, isocitrate, mannitol, apigenin, acacetin, and naringenin. The CDE exerted an antibacterial action on S. aureus isolates with minimum inhibitory concentrations ranging from 128 to 512 µg/mL. Also, CDE exhibited antibiofilm action using a crystal violet assay. A scanning electron microscope was employed to illuminate the effect of CDE on biofilm formation, and it considerably diminished S. aureus cell number in the biofilm. Moreover, qRT-PCR was performed to study the effect of CDE on biofilm gene expression (cna, fnbA, and icaA). The CDE revealed a downregulating effect on the studied biofilm genes in 43.48% of S. aureus isolates. Regarding the in vivo model, CDE significantly decreased the S. aureus burden in the liver and spleen of CDE-treated mice. Also, it significantly improved the mice's survival and substantially decreased the inflammatory markers (interleukin one beta and interleukin six) in the studied tissues. Furthermore, CDE has improved the histology and tumor necrosis factor alpha immunohistochemistry in the liver and spleen of the CDE-treated group. Thus, CDE could be considered a promising candidate for future antimicrobial drug discovery studies.